A systematic review of the toxic effects of a nanopesticide on non-target organisms: Estimation of protective concentrations using a species sensitivity distribution (SSD) approach – The case of atrazine - Hennig, Thuanne Braúlio; Bandeira, Felipe Ogliari; Puerari, Rodrigo Costa; Fraceto, Leonardo Fernandes [UNESP]; Matias, William Gerson (My University, 2023)
Nanopesticides, such as nanoencapsulated atrazine (nATZ), have been studied and developed as eco-friendly alternatives to control weeds in fields, requiring lower doses. This review contains a historical and systematic literature review about the toxicity of nATZ to non-target species. In addition, the study establishes protective concentrations for non-target organisms through a species sensitivity distribution (SSD) approach. Through the systematic search, we identified 3197 publications. Of these, 14 studies addressed “(nano)atrazine's toxicity to non-target organisms”. Chronological and geographic data on the publication of articles, characterization of nATZ (type of nanocarrier, size, polydispersity index, zeta potential), experimental design (test species, exposure time, measurements, methodology, tested concentrations), and toxic effects are summarized and discussed. The data indicate that cell and algal models do not show sensitivity to nATZ, while many terrestrial and aquatic invertebrates, aquatic vertebrates, microorganisms, and plants have high sensitivity to nAZT. The SSD results indicated that D. similis is the most sensitive species to nATZ, followed by C. elegans, E. crypticus, and P. subcapitata. However, the limitations in terms of the number of species and endpoints available to elaborate the SSD reflect gaps in knowledge of the effects of nATZ on different ecosystems.
Keywords: Ecotoxicology; Nanoherbicide; Non-target species; Protective concentrations; Risk assessment